Misdiagnosis of a twin pregnancy with double-corner uterine rupture following salpingectomy and protrusion of the amniotic sac as an adnexal cyst: a case report - Jinhua Dong; Yunfei Cao; Qiang Ma; Lili Xue; Weiying Zhu (BMC, 2020)
Abstract Background Salpingectomy-associated uterine rupture during intrauterine pregnancy is rare in the clinic. We report a case of pregnancy with bilateral rupture of the uterine horns after bilateral salpingectomy. Case presentation A 30-year-old woman of Han ethnicity presented with right epigastric pain at 28 weeks and 6 days of gestation. Examination by colour Doppler ultrasound showed the following: "Twin live births with normal foetal umbilical artery blood flow indexes and a 183 mm × 112 mm anechoic zone in the right front of the uterus". Initially, we made an incorrect judgement wherein we considered the amniotic sac that was protruding into the abdominal cavity to be an adnexal cyst. Fortunately, the diagnosis of uterine rupture was confirmed before the protruded amniotic sac broke. The mother did not bleed much, and the twin foetuses survived in our case. Conclusion A previous history of salpingectomy via laparoscopy could be a risk factor for uterine rupture in pregnant women. Attention should be paid to rare complications of pregnancy. To avoid adverse events, we should pay special attention to women with a history of laparoscopic salpingectomy who complain about abdominal discomfort and offer them a relevant ultrasound examination.